Assessing Uptake and Completion of Tuberculosis Prevention Therapy Among Healthcare Workers in Nyandarua County, Kenya - Vosevwa, Mugamangi S. (Amref International University, 2024)
Introduction: Globally, tuberculosis (TB) remains one of the leading causes of death, with healthcare workers (HCWs) at heightened risk due to occupational hazards. Tuberculosis prevention therapy (TPT) for managing latent TB infection is increasingly important worldwide and in Kenya, aligning with the WHO's vision of 'A world free of TB' and Kenya's goal to eliminate tuberculosis by 2035. This study aimed to assess the uptake and completion of TPT among HCWs in Nyandarua County, Kenya. Methodology: Utilizing both quantitative and qualitative approaches, the study included a sample of 219 HCWs from various sub-counties and levels of health facilities. Quantitative data were gathered through face-to-face interviews using a pretested structured questionnaire, while qualitative data were obtained from keyinformant interviews with one county and four sub-county TB coordinators, as well as in-depth interviews with five health facility managers. Statistical analyses included the Chi-Square test and binary logistic regression, with a p-value <0.05 indicating significance and the odds ratio used as the final measure of association. Thematic analysis was used for qualitative data. Results: Results showed that 74% of HCWs did not initiate TPT, though completion was above average, with 80% finishing the therapy. Significant factors influencing TPT uptake included health facility level (OR 28.4, 95% CI 2.7636-2.9120), awareness and training (OR 0.1, 95% CI 0.0188-0.1934), perceived TB risk (OR 7.2, 95% CI 1.14314.5088), department (OR 2.1, 95% CI 1.1055-4.0073), and having a co-worker with TB (OR 0.2743, 95% CI 0.1418-0.5304). Factors significant for TPT completion included awareness and training (OR 16.5, 95% CI 1.519-1.792) and mask-wearing (OR 0.8, 95% CI 0.979-1.334). Conclusion: The study concluded that uptake and completion of TPT could be improved through capacity building and enhanced facility-level support, and recommended that policymakers at all levels ensure adequate funding, emphasize TB risk perception and reinforce protective measures to increase TPT completion rates.
Keywords: Tuberculosis; Prevention, Tuberculosis; Nyandarua County, Kenya